2009
DOI: 10.1002/bdra.20567
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cardiac effects of maternal hyperglycemia during pregnancy

Abstract: Maternal diabetes mellitus is associated with increased teratogenesis, which can occur in pregestational type 1 and type 2 diabetes. Cardiac defects and with neural tube defects are the most common malformations observed in fetuses of pregestational diabetic mothers. The exact mechanism by which diabetes exerts its teratogenic effects and induces embryonic malformations is unclear. Whereas the sequelae of maternal pregestational diabetes, such as modulating insulin levels, altered fat levels, and increased rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 55 publications
0
95
1
3
Order By: Relevance
“…Fetal exposure to hyperglycaemia during embryogenesis, in women with poorly controlled diabetes mellitus, is known to be associated with congenital abnormalities, including congenital heart disease (CHD) [2,4,8,17]. A small increase in circulating blood glucose levels may be detrimental to the developing embryo and good glycaemic control has been shown to reduce the rate of congenital abnormalities, preterm delivery and stillbirths [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal exposure to hyperglycaemia during embryogenesis, in women with poorly controlled diabetes mellitus, is known to be associated with congenital abnormalities, including congenital heart disease (CHD) [2,4,8,17]. A small increase in circulating blood glucose levels may be detrimental to the developing embryo and good glycaemic control has been shown to reduce the rate of congenital abnormalities, preterm delivery and stillbirths [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown conclusively that maternal hyperglycemia is associated with an increased risk of mal development in the conceptus, specially neural tube and cardiac defects though the exact mechanism is not known. 6,7 Central nervous system and Gastro intestinal system including orofacial group were the most commonly involved. 8 the neural tube defects predominate in the central nervous system anomalies; the most common being meningomyelocele.…”
Section: Resultsmentioning
confidence: 99%
“…14 The human chorionic gonadotropin (hCG) secreted by the corpus luteum of pregnancy, progesterone, relaxin and human chorionic somatomammotropin (hCS) secreted by syncytiotrophoblast all increases to maintain the possible changes in pregnancy. 8,10 During first and early second trimesters of pregnancy, glucose tolerance is normal or slightly improved and peripheral (muscle) sensitivity to insulin and hepatic basal glucose production is normal. 7,9 These could be caused by the increased maternal estrogen and progesterone in early pregnancy which increase and promote pancreatic ß-cell hyperplasia (Expansion of betacell mass in response to pregnancy) causing an increased insulin release.…”
Section: Discussionmentioning
confidence: 99%
“…38,40 The most notable cardiac defects are transposition of the great arteries, mitral and pulmonary atresia, double outlet of the right ventricle, tetralogy of Fallot, and fetal cardiomyopathy. 10,25 Hyperglycemia during pregnancy can result in gestational diabetes in women with borderline or low pancreatic function. [26][27] Gestational diabetes has been associated with obstetric and neonatal problems and usually occurs in the later stages of pregnancy, that is late second and third trimester.…”
Section: Discussionmentioning
confidence: 99%